Optimal location of supplementary node in UAV surveillance system. (15th August 2019) - Li, Yue; Zhang, Yongmin; Cai, Lin
Abstract: Given the maturity of Unmanned Aerial Vehicle (UAV) technologies, UAVs have been widely used in many areas such as surveillance system. Thanks to the UAV's high mobility, not only the dynamic coverage is now achievable for surveillance systems but also the cost of building (thermal-)camera towers is reduced. The UAV surveillance system includes a UAV mesh network providing seamless monitoring. The target will be tracked down to a warning area which is a triangle formed by the three closest UAVs. A new supplementary UAV is proposed to be deployed inside the warning area to achieve a better monitoring quality. In this paper, we identify the best location of the supplementary UAV by minimizing the maximum service distance in an acute triangle. A closed-form solution is derived for the isosceles acute triangle. For arbitrary acute triangles, a real-time algorithm with low complexity, i.e., the equal service distance (ESD) algorithm, is proposed. Simulation results show that the proposed ESD algorithm can reduce the maximum service distance by up to 35.71%, 15.91%, and 21.74% compared to the incenter, circumcenter, and centroid, respectively. The optimality of the proposed approach is then validated by comparing with the exhaustive search. More simulations considering network dynamics are performed and the impacts of UAV's speed and processing time on monitoring quality are revealed.